Sealing efficiency of BeeFill 2in1 and System B/Obtura II versus single-cone and cold lateral compaction techniques - KARTAL, NEVİN; CİMİLLİ, ZÜHRE HALE (My University, 2009)
Objective: The objective of this study was to investigate the sealing properties of 2 warm vertical compaction techniques (BeeFill 2in1, System B/Obtura II) in comparison with single-cone and cold laterally compacted gutta-percha. Study design: The root canals of single-rooted human teeth were prepared by using Mtwo rotary files and divided into 4 groups (n = 10/group) with respect to the filling technique tested: Group 1, cold laterally compacted gutta-percha + AH-26; Group 2, single-cone tapered Mtwo gutta-percha + AH-26; Group 3, System B/ObturaII + AH-26; Group 4, BeeFill 2in1 + 2seal. The leakage of specimens was measured using a fluid-filtration method after 1 and 2 weeks. The data were analyzed statistically with 2-way repeated measures ANOVA (P = .05). Results: After 1 week, the System B/Obtura II group showed the greatest amount of leakage(P < .05) compared with the other test groups that had similar levels of fluid conductance(P < .05). By the end of the second week, the BeeFill group yielded the greatest amount of leakage (P < .05). Compared with their 1-week values, the fluid conductance of all test groups decreased significantly (P < .05). Conclusion: The apical sealing efficiency of System B/Obtura II and BeeFill were inferior to the other obturation techniques after 2-week fluid conductance testing in vitro. © 2009 Mosby, Inc. All rights reserved.